Association between Acid-Base Balance and Asphyxia in Newborn Infants - Sari Leyli Harahap; Chairul Adillah Harahap; Sri Sulastri; Chairul Yoel; Noersida Raid (Indonesian Pediatric Society, 1994)
We performed a prospective study on the association between acid-base balance and asphyxta based on Apgar scores in 45 newborn babies admitted to the Division of Perinatology, Pirngadi Hospital, Medan, from January 1 to February 28, 1993. Blood gas analysis was done on blood obtained from umbilical artery. Based on 1st and 5th minutes Apgar scores, 40 (88.9%) and 21 babies (46.7%, respectively, had asphyxia. Relation to acid-base balance was determined with the sensitivity of the 5th minute Apgar score in predicting acidotic states. It was found that Apgar score had sensitivity of 57.7% and specificity of 68.4% in predicting the acidotic states. Apgar score of > 7 was unable to. exclude the possible acidosis in 45% of cases (negative predictive value 54.1%). Gestational age had no influence on Apgar Scores. Apgar score was more sensitive to eliminate suspected acidosis in term neonates than in preterms. We recommend to perform umbilical arterial blood gas analysis to determine acidotic state in high risk newborn infants.